2017
DOI: 10.1016/j.socscimed.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Defining trauma in complex care management: Safety-net providers' perspectives on structural vulnerability and time

Abstract: In this paper, we delineate how staff of two complex care management (CCM) programs in urban safety net hospitals in the United States understand trauma. We seek to (1) describe how staff in CCM programs talk about trauma in their patients’ lives; (2) discuss how trauma concepts allow staff to understand patients’ symptoms, health-related behaviors, and responses to care as results of structural conditions; and (3) delineate the mismatch between long-term needs of patients with histories of trauma and the shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In the current study, over one‐third of respondents reported ACE total scores of 4 or more, the highest risk group. Therefore, as a form of social justice in action, practitioners who work with individuals with economic disadvantage and a racial or ethnic minority background would benefit from understanding the prevalence of ACE and relationship distress to support a trauma‐informed approach to care (SAMHSA, ; Thompson‐Lastad et al., ). In this case, at a minimum, family based intervention or education efforts could develop partnership with agencies/practitioners that address physical and mental health needs to more comprehensively support clients.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, over one‐third of respondents reported ACE total scores of 4 or more, the highest risk group. Therefore, as a form of social justice in action, practitioners who work with individuals with economic disadvantage and a racial or ethnic minority background would benefit from understanding the prevalence of ACE and relationship distress to support a trauma‐informed approach to care (SAMHSA, ; Thompson‐Lastad et al., ). In this case, at a minimum, family based intervention or education efforts could develop partnership with agencies/practitioners that address physical and mental health needs to more comprehensively support clients.…”
Section: Discussionmentioning
confidence: 99%
“…) and providers’ understanding of patients’ trauma (Thompson‐Lastad et al . ). The present article aims to reflect both patients’ and providers’ invocations of and reactions to choice as a mechanism for dealing with intense structural pressures.…”
Section: Methodsmentioning
confidence: 97%
“…SAMHSA's Treatment Improvement Protocol defines TIC as "a strengths-based framework that is grounded in an understanding of and responsiveness to the impact of trauma, that emphasizes physical, psychological, and emotional safety for both providers and survivors, and one that creates opportunities for survivors to rebuild a sense of control and empowerment." [80][81][82] In trauma-informed systems, the impact of trauma is recognized at all levels, and proactive policies/procedures are employed to mitigate harm and reduce the risk of retraumatization. TIC is associated with improved mental health outcomes, more effective behavior management, and enhanced safety for consumers and their care providers.…”
Section: Treat Substance Abuse Disordersmentioning
confidence: 99%